2006
DOI: 10.1152/jn.01313.2005
|View full text |Cite
|
Sign up to set email alerts
|

Role of NSF in Neurotransmitter Release: A Peptide Microinjection Study at the Crayfish Neuromuscular Junction

Abstract: Peptides that inhibit the SNAP-stimulated ATPase activity of N-ethylmaleimide-sensitive fusion protein (NSF-2, NSF-3) were injected intra-axonally to study the role of this protein in the release of glutamate at the crayfish neuromuscular junction. Macropatch recording was used to establish the quantal content and to construct synaptic delay histograms. NSF-2 or NSF-3 injection reduced the quantal content, evoked by either direct depolarization of a single release bouton or by axonal action potentials, on aver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2008
2008
2012
2012

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…Key arguments are that: (i) both NSF3 and another peptide from the external surface of the D1 domain have identical inhibitory effects on both ATPase activity and synaptic transmission; and (ii) mutation of the glycine residue, which inhibits NSF function in vivo (32,33), completely abolishes the ability of NSF3 to inhibit both ATPase activity and synaptic transmission (28). Mass spectroscopy reveals that exposure to UV light produces a peptide that is identical to noncaged NSF3 (unpublished data), so that the biochemical properties of NSF3 defined in previous work (28,31) should fully apply to uncaged cNSF3. Nonetheless, to consider possible side effects of uncaging cNSF3, we performed two control experiments.…”
Section: Resultsmentioning
confidence: 75%
See 1 more Smart Citation
“…Key arguments are that: (i) both NSF3 and another peptide from the external surface of the D1 domain have identical inhibitory effects on both ATPase activity and synaptic transmission; and (ii) mutation of the glycine residue, which inhibits NSF function in vivo (32,33), completely abolishes the ability of NSF3 to inhibit both ATPase activity and synaptic transmission (28). Mass spectroscopy reveals that exposure to UV light produces a peptide that is identical to noncaged NSF3 (unpublished data), so that the biochemical properties of NSF3 defined in previous work (28,31) should fully apply to uncaged cNSF3. Nonetheless, to consider possible side effects of uncaging cNSF3, we performed two control experiments.…”
Section: Resultsmentioning
confidence: 75%
“…Our strategy was based on incorporating a caging group onto a key amino acid of a peptide that blocks the ␣SNAP-stimulated ATPase activity of NSF in vitro (28)(29)(30). This peptide prevents the NSF-mediated disassembly of the SNARE complex (30) and inhibits neurotransmitter release when injected into presynaptic terminals (28,31). By using this caged peptide to perturb NSF function, we found that the amount of neurotransmitter release was inhibited with a latency ranging from 1.6 to 3.2 s. Furthermore, the kinetics of neurotransmitter release was decreased even more rapidly, with a latency of 0.2 s. These very rapid actions of the uncaged inhibitory peptide lead us to conclude that the physiologically relevant locus of NSF action in the SV cycle is immediately upstream of membrane fusion and release of neurotransmitter.…”
mentioning
confidence: 99%
“…The SNAP protein NAPB (2 A1 and 2 H2) recruits NSF to membranes for vesicle fusion and exocytosis (i.e., for neurotransmitter release) (100). NSF itself also decreased here after H2, which could have antiexcitotoxic pre-and postsynaptic consequences via decreased glutamate release (77) and decreased stabilization of AMPA glutamate receptors in the postsynaptic membrane (6), respectively. SH3GL1 decreased after A1; this protein may be needed for vesicle fusion in the presynaptic terminal (86).…”
Section: Prevention Of Excitotoxicity In Cerebellum: Decreased Excitamentioning
confidence: 99%
“…NSF is required for the disassembly and recycling of SNARE proteins during the interval between exocytosis and endocytosis, an event important for maintaining normal neurotransmitter release in presynaptic termini (Schweizer, Dresbach et al 1998; Littleton, Barnard et al 2001; Parnas, Rashkovan et al 2006). NSF is also important for synaptic plasticity, which is believed to be the cellular mechanism for the formation of memory.…”
Section: Discussionmentioning
confidence: 99%